Progress in indentation study of materials via both experimental and numerical methods - Zhou, Kun (2018)
Indentation as a method to characterize materials has a history of more than 117 years. However, to date, it is still the most popular way to measure the mechanical properties of various materials at microscale and nanoscale. This review summarizes the background and the basic principle of processing by indentation. It is demonstrated that indentation is an effective and efficient method to identify mechanical properties, such as hardness, Young’s modulus, etc., of materials at smaller scale, when the traditional tensile tests could not be applied. The review also describes indentation process via both experimental tests and numerical modelling in recent studies.